War and Law in the Islamic World - Vanhullebusch, Matthias (Brill's Arab and Islamic Laws Series, 2015)
Armed conflict, today, has diverged from war as it was known in generations past, and from this, has tested the means by which conflicts and violence are regulated. Written with an eye to a region plagued by such conflicts, War and Law in the Islamic World examines the origins and roles that two distinct systems of governance - Islamic law and international humanitarian law - have played in conflicts past and present. Meant equally for the scholar or student, this book presents the legal and policy complexities of today's conflicts in a new light through its careful and well-researched investigation of the past and the present.